Prognostic performance of ferritin in combination with CT-SS and NEWS, to predict ICU admission and mortality in COVID-19 - Daş, Murat; Beyazıt, Fatma; Bardakcı, Okan; Ünal Çetin, Ece; Akdur, Gökhan; Akman, Canan; Akdur, Okhan; Beyazıt, Yavuz (The Journal of Infection in Developing Countries, 2026)
Introduction: The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has created significant challenges in predicting severe disease outcomes. This study evaluates the combined prognostic performance of serum ferritin, national early warning score (NEWS), and computed tomography severity score (CT-SS) in predicting intensive care unit (ICU) admission and 30-day mortality. Methodology: This retrospective study included 693 COVID-19 patients with confirmed RT-PCR results and complete medical records. Demographic, clinical, and laboratory data, including ferritin levels, NEWS, and CT-SS, were analyzed. Statistical analyses were conducted to evaluate their individual and combined predictive capabilities. Results: Elevated ferritin levels, higher NEWS, and greater CT-SS were significantly associated with increased ICU admission and mortality risks. Receiver operating characteristic (ROC) analysis revealed excellent predictive accuracy for mortality: ferritin (area under the receiver operating characteristic curve [AUROC]: 0.916), NEWS (AUROC: 0.927), and CT-SS (AUROC: 0.881). Integrating ferritin into NEWS and CT-SS models enhanced predictive precision, with combined scoring systems yielding the highest odds ratios for adverse outcomes. Patients with a NEWS ≥ 5 and ferritin level ≥ 275.8 had a 151-fold increased risk of mortality, while those with a CT-SS ≥ 9 and ferritin level ≥ 275.8 had a 72-fold increased risk. Conclusions: Combining ferritin with NEWS and CT-SS improves the prognostic accuracy for predicting severe outcomes in COVID-19 patients. This study emphasizes the value of integrating laboratory markers with established scoring systems to optimize clinical decision-making. The findings can guide early interventions, reduce mortality, and improve resource utilization during pandemics.